Intramedullary versus extramedullary fixation for the treatment of subtrochanteric fracture: A systematic review and meta-analysis. (March 2019) - Xie, Huanguang; Xie, Linzhen; Wang, Jinwu; Chen, Chunhui; Zhang, Chuanxu; Zheng, Wenhao
Abstract: Purpose: This meta-analysis was performed to investigate the outcomes of intramedullary fixation versus extramedullary fixation in the treatment of subtrochanteric fracture from the current literature. Methods: The electronic literature database of PubMed, Embase, Cochrane library, CNKI and Wanfang were searched in December 2018. The data operation time, intraoperative blood loss, length of incision, length of stay, union time, rate of infection, rate of fixation failure, rate of refracture, rate of reoperation, rate of nonunion and rate of excellent and good results were extracted. Stata 14.0 software was used for our meta-analysis. Results: A total of 11 studies including 8 RCTs and 3 cohort studies met our inclusion criteria. This meta-analysis showed that intramedullary fixation could achieve significantly shorter operation time (P = 0.000), less intraoperative blood loss (P = 0.000), shorter length of incision (P = 0.000) and length of stay (P = 0.001) with evidently lower rate of fixation failure (P = 0.001), rate of reoperation (P = 0.003) and higher rate of excellent and good functional results (P = 0.003) than extramedullary fixation for subtrochanteric fractures. However, no significant difference was found regarding union time (P = 0.17), rate of infection (P = 0.99), rate of refracture (P = 0.98) and rate of nonunion (P = 0.42) between the two groups. Conclusion: Our meta-analysis suggested that intramedullary fixation for subtrochanteric fracture might be superior to extramedullary fixation in term of shorter operation time, less intraoperative blood loss, shorter length of incision, length of stay and better functional outcomes. Meanwhile, intramedullary fixation had lower rate of fixation failure and reoperation. Therefore, we recommend intramedullary fixation as the treatment of subtrochanteric fracture. More large multi-center and high-quality RCTs are required for further research. Highlights: This meta-analysis was to investigate intramedullary fixation versus extramedullary fixation in subtrochanteric fracture. Intramedullary fixation is superior in term of operation time, intraoperative blood loss, length of incision, length of stay and functional outcomes. Intramedullary fixation had lower rate of fixation failure and reoperation.